Cryptococcus’ colony forming unit count usefulness: Español (Actualizaciones en Sida e Infectología, 2022)
Background. The Cryptococcus´ colony-forming unit (CFU) count in cerebrospinal fluid (CSF) would be a reliable marker for patient prognosis and a simple and inexpensive tool. Objective. To evaluate the usefulness of the CFU count of Cryptococcus spp. And to compare it with the variations of Cryptococcus´ capsular antigen (CrAg) in CSF.Materials and methods. Clinical records of patients with aids-related meningoencephalitis caused by Cryptococcus  assisted in our center between February 2016 and July 2020 were reviewed. CFU count and CrAg values ​​in CSF were evaluated during the evolution of the mycosis.Results and Discussion. Data from 94 clinical episodes of 85 patients with a total of 297 observations of CSF samples were analyzed.The importance of using the CFU count was evidenced as it is a viability and fungal load marker.Low CFU count did not necessarily coexist with low CrAg.Regarding the evolution over time, most of the patients were diagnosed with a high fungal load and its decrease occurred faster than that the one of AgCr. This would reflect the improvement of the patient, allowing behaviors to be taken in this regard.
Keywords: criptococosis; ufc/mL